Cyclophosphamide alters the tumor cell secretome to potentiate the anti-myeloma activity of daratumumab through augmentation of macrophage-mediated antibody dependent cellular phagocytosis. (1st January 2021) - Naicker, Serika D; Feerick, Claire L; Lynch, Kevin; Swan, Dawn; McEllistrim, Cian; Henderson, Robert; Leonard, Niamh A; Treacy, Oliver; Natoni, Alessandro; Rigalou, Athina; Cabral, Joana; Chiu, Christopher; et al.
ABSTRACT: Multiple Myeloma (MM) is a malignant disorder of plasma cells which, despite significant advances in treatment, remains incurable. Daratumumab, the first CD38 directed monoclonal antibody, has shown promising activity alone and in combination with other agents for MM treatment. Daratumumab is thought to have pleiotropic mechanisms of activity including natural killer (NK) cell-mediated antibody-dependent cellular cytotoxicity (ADCC). With the knowledge that CD38-expressing NK cells are depleted by daratumumab, we sought to investigate a potential mechanism of enhancing macrophage-mediated antibody-dependent cellular phagocytosis (ADCP) by combining daratumumab with cyclophosphamide (CTX). Cyclophosphamide's immunomodulatory function was investigated by conditioning macrophages with tumor cell secretome collected from cyclophosphamide treated MM cell lines (CTX-TCS). Flow cytometry analysis revealed that CTX-TCS conditioning augmented the migratory capacity of macrophages and increased CD32 and CD64 Fcγ receptor expression on their cell surface. Daratumumab-specific tumor clearance was increased by conditioning macrophages with CTX-TCS in a dose-dependent manner. This effect was impeded by pre-incubating macrophages with Cytochalasin D (CytoD), an inhibitor of actin polymerization, indicating macrophage-mediated ADCP as the mechanism of clearance. CD64 expression on macrophages directly correlated with MM cell clearance and was essential to the observed synergy between cyclophosphamide and daratumumab, as tumor clearance was attenuated in the presence of a FcγRI/CD64 blocking agent. Cyclophosphamide independently enhances daratumumab-mediated killing of MM cells by altering the tumor microenvironment to promote macrophage recruitment, polarization to a pro-inflammatory phenotype, and directing ADCP. These findings support the addition of cyclophosphamide to existing or novel monoclonal antibody-containing MM regimens.